Medical Student’sPerceptions Toward Integrated Histology Practical Class: A Quantitative and Qualitative Study - Syaidah, Rahimi; Sukmawati, Dewi; Edison, Rizki Edmi; Jusuf, Ahmad Aulia (International Journal of Human and Health Sciences (IJHHS), 2020)
Objectives : This study was performed to gain an understanding about perceptions of integrated practical class between histology and anatomical pathology among medical students in Universitas Indonesia, and to evaluate the quality of current histology learning method. Materials and Methods: The students learnt histology by means of histology alone or integrated with anatomical pathology. Two hundred and fifty-seven students (n=257) completed the anonymous questionnaire-based survey. The post-test’s score from the last two years were achieved and compared from the archive. Results and Discussion: The results of the study revealed two contrasting perceptions; while the majority of the students agreed that this learning method was considered useful, it nevertheless brings a great deal of stress considering the amount of materials they have to learn in short time. This generates a range of negative feelings in students that affected their learning performance Conclusion : Integrating the subjects is an effective way to improve students understanding of normal and abnormal condition of an organ. However, this method requires a longer time for students to understand the crowded material for the effectiveness. Further research is needed to refine the better strategy to deliver the integrated histology material effectively. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 200-205